Penyusunan Lakon Sudarsana Labuh Sebagai Media Penyampai Nilai-nilai Kemanusiaan - Widyastoto, Pranowo Aryo; Harti, Sri (Institut Seni Indonesia Surakarta, 2023)
The article with the title Penyusunan Lakon Sudarsana Labuh Sebagai Media Penyampai Nilai-Nilai Kemanusiaan (Preparation of Lakon Sudarsana Labuh As A Medium For Transmitting Human Values) is an effort to explore the human values contained in the character Sudarsana as outlined in the wayang madya performance. This research uses the pakeliran padat concept approach and the theory of sanggit lakon, the idea of Sugeng Nugroho, which is used in the creation of lakon “Sudarsana Labuh”. Sudarsana, the main character in this work, is one of the children of Parikesit who lives with Begawan Druwasa, his grandfather, in the Jatipitu hermitage. One day he wanted to serve the country but experienced various problems that arose both from within and outside himself. Sudarsana’s efforts in resolving these various problems ultimately became a ground for interpretation to explore human values, in this case selfless sacrifice. The preparation of this work went through 3 stages, namely orientation, observation and exploration. Orientation includes searching for information both verbally and in writing. Observation is an in-depth observation carried out by the writer to adjust the theme, main idea and lakon, and exploration, namely pouring everything obtained in the previous stages into a script and wayang performance. The results of the observations are (1) Sudarsana’s sincere desire to defend the Yawastina State, (2) Sudarsana’s sacrifice in protecting the state which is symbolized by saving the king from danger, (3) Sudarsana’s motivation to defend the state.